Методика формализации обобщенного полиальтернативного трехмерного прямого анализа данных синтетического учета расходов как основы информационной технологии аудита - Нескородева, Татьяна Васильевна (НТУ "ХПИ", 2016)
Определена структурная модель обобщенных закономерностей данных синтетического учета расходов как основа автоматизации полиальтернативного анализа на противоречивость по характеристикам разнообразия и масштабов деятельности предприятия, равномерности и непрерывности, предельных состояний, совершения однотипных операций на верхнем уровне. Cформированы функциональные модели обобщенного полиальтернативного прямого анализа данных синтетического учета расходов по направлениям преобразований подчиненных предпосылкам бухгалтерского учета «осмотрительность», «полнота», «периодичность» как основы ИТ многоуровневой СППР аудита с полиальтернативными критериями оценивания соблюдения данных предпосылок.

The structural model of generalized regularities of synthetic accounting cost data as the basis for the automation of polyalternative analysis of the contradictory characteristics a variety and scale of the enterprise, the uniformity and continuity, limit states, committing of the same operations on the upper level is defined. Formalized the set of alternatives to select subsets of the data with the direct analysis on the inconsistency of three prerequisites Provisions (standards) of accounting (P(s)A): "circumspection", "completeness", "periodicity". The structural model of a set of alternatives to select subsets and the generated functional model of the generalized polyalternative direct analysis of the data of synthetic accounting costs development subordinates according to the assumptions of the framework as it multi-level DSS audit polyalternative the criteria for evaluating compliance with preconditions P(s)A. The possibilities and benefits of applying the proposed methodology: polyalternative automation of data analysis on the inconsistency of the four kinds of characteristics of the enterprise; ability to identify various techniques of fraud through the implementation of polyalternative analysis of the patterns; opportunity to consider features of the operating activities of a company (different industry, technology, etc.)and system control on the types, phases and periods of work due to the possibility of a set of alternatives matched sets; to reduce the volume of analyzed data or the actual test at the lower levels due to separation of subsets with signs of fraud in the upper levels; to carry out a dialogue with decision makers in the language of the subject area through the formalization of directions of data transformations under the assumptions P(s)A.
The technique of formalization of the generalized three-dimensional polyalternative direct analysis of the data of synthetic accounting costs as the basis for information technology audit
Keywords: финансово-экономическая деятельность; обобщенные закономерности; сопоставляемые множества; предпосылки бухгалтерского учета; set of generalized regularities; preconditions accounting; synthetic accounting; information technology; multi-level DSS audit technique